Childhood emotional incest scale: assessing its psychometric properties in Bangladesh - Ahona, Nafiza Nawar; Nigar, Naima (Dhaka University Journal of Biological Sciences, 2025)
The Childhood Emotional Incest Scale (CEIS), developed by Çimşir and Akdoğan(1), is a 12-item scale that was designed to measure the construct of emotional incest. The current research aimed to investigate this matter, raising awareness and adapting the newly developed scale to the Bangladeshi culture. One hundred eighty-six participants were chosen, of which 123 were females and 63 males, and 181 responses were later used for analysis after excluding outliers. The participants were adults, ranging in age from 19 to 36 years old. Inter-item correlation, validity, reliability, and factor analysis were computed, revealing that the scale exhibited good inter-item and inter-factor validity, as well as a high reliability (Cronbach's α = 0.891). Three factors were extracted following the factor analysis: Unsatisfactory Childhood, Surrogate Spouse, and Parentification. Overall, the scale was proven to be an excellent measure for the construct and can be used for further study in this area. Dhaka Univ. J. Biol. Sci. 34(2): 103-116, 2025 (July)